Electrodermal reactivity in an aversive countdown task: Concurrent and prospective relations with triarchic psychopathy traits and antisocial behavior outcomes in a child-aged sample - Bertoldi, Bridget M.; Patrick, Christopher J.; Yancey, James R.; LaManna, Rachel; Tuvblad, Catherine; Oskarsson, Sofi; Baker, Laura A.; Raine, Adrian; Fowles, Don (Frontiers in Psychiatry, 2025)
IntroductionConsiderable evidence exists for reduced electrodermal reactivity to aversive cues/events in high-psychopathic individuals, but most research of this kind has employed adult samples and cross-sectional designs. The current study examined skin conductance (SC) activation during anticipation of and in response to a noise stressor in a sample of 9–10 year old children in relation to constituent traits of psychopathy described by the triarchic model (i.e., boldness, disinhibition, meanness), both concurrently and at a five-year follow-up, and in relation to antisocial behavior at the follow-up.MethodsParticipants were 1,082 children from the greater Los Angeles area who underwent successive waves of testing in a longitudinal twin project. Current study analyses focused on (a) SC from the noise stressor task and parental ratings of children’s triarchic traits collected at wave 1 of the project (W1; ages 9-10), and (b) parent- and child-ratings of the triarchic traits along with child-reported engagement in aggressive and nonaggressive antisocial behavior (ASB) collected at wave 3 (W3; ages 14-15).ResultsReduced SC reactivity in the noise-stressor task at W1 was related to parent-rated boldness both concurrently (at W1) and prospectively (at W3), but not to parent-rated disinhibition or meanness at either wave. Interestingly, reduced SC reactivity at W1 showed associations with both boldness and meanness as rated by child participants themselves at W3. Additionally, reduced W1 SC reactivity was uniquely predictive of child-reported nonaggressive ASB at W3, whereas W1 parent-rated boldness was uniquely predictive of child-reported aggressive behavior at W3.DiscussionOur finding of an inverse relationship between SC reactivity and parent-rated boldness at W1 corroborates evidence from prior adult research and points to low fear (threat sensitivity) as the basis of deficient stress responding in psychopathy. The finding of contrasting predictive relations for W1 SC reactivity and W1 parent-rated boldness with ASB at W3 suggests differing roles for elements of threat sensitivity tapped by each (e.g., low anxiousness versus social dominance) in nonaggressive versus aggressive forms of ASB. Our findings highlight the nuances of dispositional fearlessness as construct of relevance to psychopathy and suggest important avenues for future research.